„Íme, így szól hozzánk a múlt útmutatása.” Egyháztörténelmi hivatkozások használata egyházpolitikai szándékok igazolására (1946) - LÁNYI, Gábor János (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
“Behold, the Guidance of the Past Speaks to Us”. Using References to Church History to Justify Church Policy (1946). Based on László Kósa’s suggestion that historical reference is an important element of communal identification in the Reformed Church, our study examines how the Hungarian Reformed recalled the memory of the Szatmárnémeti Synod of three hundred years ago in their renewal efforts following World War II. Through the analysis of three public speeches, our study illustrates how the church’s past was used to strengthen its present practices. In his New Year’s address, Bishop János Vásárhelyi of Transylvania stresses that the 1646 Szatmárnémeti Synod established order and warned of the importance of obedience. In other words, in Vásárhelyi’s interpretation, the institutions must control the movement. Aladár Szabó, during the summer of 1946, draws the lesson from the Szatmárnémeti Synod that it was an example of the inability of the institution to control the movement, which had a renewing effect without it. Finally, Bishop László Ravasz, in his episcopal report in November 1946, shows the eternal dialectic of movement and institution in the history of the Church and sees the lesson of the Szatmárnémeti Synod as that the institution had apparently won, but in reality, the movement had been legalized. According to Ravasz, the correct relationship between movement and institution is that the institution saves the movement from becoming a sect, while the movement can revive the institution burnt out by institutionalization. Our study also points out that the different interpretations of the commemoration of the Szatmárnémeti Synod also reflect the National Reformed Free Council movement, which began in 1946 to challenge the church government of Ravasz.